The ‘Soil of the Year’ Campaign in Germany—Experiences from over 20 Years of Public Relations Work for Soil Awareness - Sonja Medwedski; Gerhard Milbert; Maike Bosold; Jeannette Mathews; Klaus Kruse (Land, 2025)
Since 2005, the ‘Soil of the Year’ campaign has aimed to highlight the ecological functions and societal relevance of soils in Germany. This article analyses the campaign’s concept, evolution and outreach strategies. It evaluates its role as a tool for environmental education, public engagement and policy communication. Over two decades, the initiative has established itself as a key platform connecting science, policy and society. The annual designation of a specific soil type enables focused communication, enhances public understanding and encourages sustainable soil management. The article concludes by identifying success factors for the long-term effectiveness of the campaign and outlines future opportunities for interdisciplinary collaboration and digital innovation. In addition, the findings provide actionable recommendations for similar soil awareness campaigns in other countries.